Bio-Conjugated Metallic Complexes in Drug Design - Patle, Dilend; Sengar, Narendra Pratap Singh (Indian Journal of Pharmaceutical Education and Research, 2025)
Background This comprehensive review highlights the importance of bio-conjugated metallic complexes in drug design, particularly in the field of metallo-pharmaceutical science. The review emphasizes the need for biological relevance and the coordination of biomolecules or modified bio-compounds with metallic systems to maximize drug action and minimize toxicity. Materials and Methods The objective of this review is to discuss various diseases, which exemplify the potential of bio-conjugated metallic complexes as a promising approach for drug design. Results Utilizing physiologically active ligands in metal complexes has demonstrated improved antioxidant, antiviral, antitubercular and antitumor effects. Conclusion Bio conjugated systems have become a viable method for creating molecules with several uses that are good for human health. The development of metal-based imaging agents and drug delivery systems has increased due to the conjugation of metals with biologically active compounds.
Keywords: Bio-conjugation; Metallic complexes; Drug design; Metallo-pharmaceutical science; Antioxidants; Chelate